How do vocational teachers keep up to date with trends in pedagogy and in industry? - Smith, Erica [Verfasser] (My University, 2019)
"This chapter examines the important topic of the 'dual professionalism' of VET teachers in Australia. How, exactly, do they develop further and keep up to date in their industries and in pedagogy? Drawing sub-sets of material from a major national research project, the chapter provides survey evidence from over 900 VET teachers as well as detailed interview data from three case study training providers. The results show a high level of commitment to professional development, both formal and informal, particularly in teachers' industry areas, sometimes relating to licensing or regulatory requirements within those industries. Some teachers undertook multiple professional development activities each year and were willing to pay for their own development. There was, however, some resistance to development activities that were perceived to relate primarily to compliance with regulatory regimes. The chapter proposes a matrix to represent engagement in types of professional development and then problematise this model through discussion of the resistance and relating it to earlier debates around competency-based training." (author's abstract; BIBB-Doku)
Keywords: P 3.2.3 Lehrer; I 2.3.5 Australien, Ozeanien; Berufsschullehrer; Professionalisierung; Lehrerbildung; Australien